Olhos fechados : a perspectiva de pais sobre bullying - Floria, Mariana Simões (Universidade Federal de São Carlos, 2015)
The parents perspective of bullying is still a subject little explored in the literature. This study aimed to investigate knowledge s parents about bullying and compare their own report on the involvement of children with the information obtained by means of their own children, teachers and peers. Eighty students (6 to 8 years) of a public school in São Paulo accounted School Violence Scale and Sociometric Indication Protocol. Four teachers and eight pairs answered a questionnaire investigating the involvement of students in bullying. Thirty-nine parents (79,5% female, mean age 37 years) completed a questionnaire, structured according to the study objectives. The results indicate that the frequency of involvement in bullying pupils is above 40% of the sample. About 13% of parents say that their children were involved in bullying, while 7.5% of teachers and 17.5% of couples reported the same. Parents point out more consequences for the victim status. Few parents cited bullying involvement indicators, and the son of the report was the main criterion for judging the involvement of the same. Some procedures adopted by parents on the involvement of children were talking to their children, look for school managers and health professionals. According to the account of their parents, most of the children were involved in bullying for more than two years. Even with the use of different instruments to assess involvement in bullying and use of a questionnaire not validated to investigate the perspective of parents, this study also represents a significant advance for the area. Further investigation could be carried out to evaluate the effectiveness of the procedures adopted by the parents before the child's involvement.
Keywords: Violência escolar; Bullying; Pais e filhos; Perspectiva; Bullying; Parents; Perspective; CIENCIAS HUMANAS::PSICOLOGIA